Towards an amplitude analysis of the decay Λ b 0 → pK − γ $$ {\varLambda}_b^0→ {pK}^{-}γ $$ - Johannes Albrecht; Yasmine Amhis; Anja Beck; Carla Marin Benito (Journal of High Energy Physics, 2020)
Abstract The helicity formalism applied to the radiative decay Λ b 0 → pK − γ $$ {\varLambda}_b^0→ {pK}^{-}γ $$ is presented for the first time in this paper. The aim is to provide the necessary formalism to be able to resolve the resonant pK − structures at the photon pole by means of an amplitude analysis. Experimental effects, such as resolution, are also discussed.